Involvement of Immune Responses in the Efficacy of Cord Blood Cell Therapy for Cerebral Palsy - Kang, Mino; Min, Kyunghoon; Jang, Joonyoung; Kim, Seung Chan; Kang, Myung Seo; Jang, Su Jin; Lee, Ji Young; Kim, Sang Heum; Kim, Moon Kyu; An, SeongSoo A; Kim, MinYoung (Stem cells and development, 2015)
This study evaluated the efficacy of umbilical cord blood (UCB) cell for patients with cerebral palsy (CP) in a randomized, placebo-controlled, double-blind trial and also assessed factors and mechanisms related to the efficacy. Thirty-six children (ages 6 months to 20 years old) with CP were enrolled and treated with UCB or a placebo. Muscle strength and gross motor function were evaluated at baseline and 1, 3, and 6 months after treatment. Along with function measurements, each subject underwent (18)F-fluorodeoxyglucose positron emission tomography at baseline and 2 weeks after treatment. Cytokine and receptor levels were quantitated in serial blood samples. The UCB group showed greater improvements in muscle strength than the controls at 1 (0.94 vs. -0.35, respectively) and 3 months (2.71 vs. 0.65) after treatment (Ps<0.05). The UCB group also showed greater improvements in gross motor performance than the control group at 6 months (8.54 vs. 2.60) after treatment (P<0.01). Additionally, positron emission tomography scans revealed decreased periventricular inflammation in patients administered UCB, compared with those treated with a placebo. Correlating with enhanced gross motor function, elevations in plasma pentraxin 3 and interleukin-8 levels were observed for up to 12 days after treatment in the UCB group. Meanwhile, increases in blood cells expressing Toll-like receptor 4 were noted at 1 day after treatment in the UCB group, and they were correlated with increased muscle strength at 3 months post-treatment. In this trial, treatment with UCB alone improved motor outcomes and induced systemic immune reactions and anti-inflammatory changes in the brain. Generally, motor outcomes were positively correlated with the number of UCB cells administered: a higher number of cells resulted in better outcomes. Nevertheless, future trials are needed to confirm the long-term efficacy of UCB therapy, as the follow-up duration of the present trial was short.